ESTUDO DO COMPORTAMENTO DE SOLO ARGILOSO ESTABILIZADO COM MATERIAL FRESADO A PARTIR DO ENSAIO CBR - Batezini, Rafael; Gonçalves, Fernando J. P.; Porto, Eliara; Ferreira, Matheus C. (Salão do Conhecimento, 2013)
Resumo